Geoelectrical monitoring: an innovative method to supplement landslide surveillance and early warning. Issue 1 (1st September 2013) - Supper, Robert; Ottowitz, David; Jochum, Birgit; Kim, Jung‐Ho; Römer, Alexander; Baron, Ivo; Pfeiler, Stefan; Lovisolo, Mario; Gruber, Stefanie; Vecchiotti, Filippo
ABSTRACT: Permanent geoelectrical monitoring, using the GEOMON 4D instrumentation in combination with high resolution displacement monitoring by means of the D.M.S. system, was performed at two active landslide areas: Ampflwang/Hausruck in Austria, and Bagnaschino in Italy. These sites are part of the Austrian geoelectrical monitoring network, which currently comprises six permanently monitored landslides in Europe. Within the observation intervals, several displacement events, triggered by intense precipitation, were monitored and analysed. All of these events were preceded by a decrease of electric resistivity. The application of an innovative 4D inversion algorithm made it possible to investigate the potential processes which led to the triggering of these events. We conclude that resistivity monitoring can significantly help in the investigation of the causes of landslide reactivation. Since the results also contribute to the extrapolation of local displacement monitoring data to a larger scale, resistivity monitoring can definitely support decision‐finding in emergencies.